Meat processing and handling facilities in slaughterhouses of selected areas of Bangladesh - Alam, MA; Hasan, MT; Hossain, MD; Ahemd, S; Hoque, SAM; Hossain, MM; Rahman, SME (Bangladesh Journal of Animal Science, 2022)
The study was conducted to investigate the present status of meat processing facilities in different slaughterhouse of Bangladesh through field survey. The data was collected through interview schedule selecting 30 respondents (Butcher, Seller and Consumer) in Khulna, Rajshahi and Rangpur Division in Bangladesh. They were asked about knowledge of hygienic meat production, slaughterhouse environment, existing facilities, sanitation and waste management, opinion of the butcher, seller and consumers. It was obtained from the study indicating that approximately 75.63% of the animals were slaughtered at the abattoir. Only 5.8% of butchers (n=30) knew about the production of hygienic meat. Almost 100% of the abattoirs lacked hygiene and sanitation. Only 26.66% slaughtered carcasses were checked by veterinary surgeon where another 16.7% were checked by unskilled meat inspectors from the municipality. Only 23.33% of slaughterhouses were situated in environmentally friendly locations. Consumer perception revealed that only 3.33% of consumers have knowledge of meat hygiene. Meat is a great source of animal protein in our country but hygienic condition and facilities available in slaughterhouse were not satisfactory. Slaughterhouses both in rural or municipal areas were contaminated frequently and therefore meat and meat byproducts coming from such conditions often deteriorated through bacterial infection or contamination might be the cause of food poisoning or diseases in consumers. Bangladesh Journal of Animal Science 51 (3): 115-121, 2022